Práctica de valores en los docentes de educación básica de dos instituciones educativas públicas de la DREC - Callao - Flores Figueroa, Marcos Roel (2010)
The aim of this study was to describe the values that are practiced in basic education teachers from two public educational institutions DREC-Callao. The study involved 74 teachers: 12 of primary level and 62 of secondary level of both genders, for morning and afternoon shifts, the age of participating teachers were between 23 and 50 years. To measure the practice of teaching values of the questionnaire was used practice of the values proposed by Cordova (2007) carried out on the same tests of validity and reliability for research purposes. Given the research design, the results allowed us to describe that teachers practice the values of honesty, respect, responsibility, solidarity and punctuality in a range from fair to excellent.